Estimation of morphological and molecular genetic diversity in blackgram [Vigna mungo (L.) Hepper] under YMV hotspot regime - M. Vignesh, S. Jeevitha, R. Karthikeyan,; A. J. Nainu, A. Malarkodi, R. Tirumalai,; S. Murugan, R. Anandan, M. Prakash, (Horticultural Biotechnology Research)
A phenotypic and molecular diversity study was conducted using seven traits and 19 SSR markers in a collection of 26 black gram genotypes. Phenotypic characterization was based on seven yield and yield related variable. The field experiment was laid out at Panboli village (YMV hotspot) of Tirunelveli District in Tamilnadu during summer 2017. Genetic divergence was estimated on the basis of D2 values and 26 genotypes under study were grouped into six clusters by Tocher’s method. Seed yield per plant followed by Plant height and number of pods per plant contributed to the genetic divergence. The genetic distance announced using DICE dissimilarity co-efficient indicated highest divergence of 1.0 between VBN 8 and AUBG 17 and between VBN 8 and AUBG 19. The dendogram constructed using the DICE dissimilarity co-efficient between genotypes showed four apparent clusters based on marker allele distribution. Divergence was noted between the dissimilarity matrices based on the molecular and phenotypic diversity based on agronomic data.